Evaluation of heat transfer performance of a heat exchanger tube mounted with an I-rib twisted tape and twisted winglets - Wenxuan Qiu; P. Samruaisin; V. Chuwattanakul; Naoki Maruyama; Masafumi Hirota; Smith Eiamsa‐ard (Scientific Reports, 2025)
This study aims to improve the efficiency of heat exchangers and explore the enhancement mechanism of the thermal performance characteristics of heat exchange tubes by I-rib twisted tapes and twisted winglets (I-RTTW) through experimental research and numerical simulation. The I-RTTW structure consists of a central I-type rib and an edge twisted winglet. The key geometric parameters of the edge twisted winglet include the wing depth ratio (d/W = 0.096, 0.13, 0.16), the wing width ratio (w/W = 0.096, 0.13, 0.16), and a fixed twist angle of 45°. The study uses air as the working fluid to systematically analyze the heat transfer performance of the I-RTTW over a range of Reynolds numbers (Re) of 6,000-20,000. The experimental results reveal that the I-RTTW significantly improves heat transfer through a dual mechanism. First, the edge twisted winglet effectively disrupts the fluid boundary layer by inducing secondary flows. Second, the central I-type rib can promote radial mixing of the fluid. Further in-depth analysis of the experimental data revealed that a greater winglet depth ratio (d/W) increases the longitudinal size of the cutting winglet, thereby disturbing the fluid more deeply and increasing boundary layer disruption. An increased winglet width ratio (w/W) significantly enhances the fluid mixing effect by expanding the lateral coverage, thereby reducing thermal resistance and enhancing heat transfer between the pipe wall and the fluid. In terms of flow resistance characteristics, a greater winglet depth ratio directly leads to an increased longitudinal size of the cutting winglet. This strengthens the disturbance of fluid, resulting in increased boundary layer separation and greater eddy losses. Similarly, an increased winglet width ratio leads to greater lateral flow resistance, so that the fluid needs to overcome a larger shear force and higher collision losses. This leads to an increased friction coefficient (f). In the current study, the heat transfer rate of a pipe equipped with I-RTTWs is about 7 to 26% and 68 to 99% higher than that of a pipe equipped with typical tape (TT) and the plain tube, respectively. The friction coefficient is 1.15-1.37 times and 3.46-4.12 times that of a TT and plain tube, respectively. The comprehensive thermal performance index of the pipe with an I-RTTW is as high as 1.29.
Keywords: Heat Transfer and Optimization; Heat Transfer Mechanisms; Solar Thermal and Photovoltaic Systems